Clinico-epidemiological Profile of Primary Brain Tumours in North-Eastern Region of India:A Retrospective Single Institution Study - Paul, Moumita; Goswami, Smriti; C, Goutham Raj; Bora, Ghritashee (Asian Pacific Journal of Cancer Care, 2023)
Background: Brain tumours are mixed group of neoplasms originating from the intracranial tissues. The two basic types of brain tumours are primary and metastatic tumours. Very little is known about the epidemiology of primary brain tumours in the North-Eastern region of India. We carried out a 5-year retrospective study on the epidemiology of the primary brain tumour treated in our hospital. Aim: To study the clinico-epidemiological patterns of brain tumour in a tertiary care center in North-Eastern region of India. Materials and Methods: A retrospective epidemiological approach has been used. The records of patients registered in our hospital from 2017-2022 diagnosed as primary brain tumours have been selected. Data regarding age,sex,site of the tumour, histology, geographical distribution and treatment delivered have been collected. Results: Out of a total of 100 patients studied, males (68%) outnumbered females (32%) with a male:female ratio of 2.1:1. Frequency of brain tumours was found to be higher in the age group 31-40 years i.e. 23% compared to age groups 21-30 years and 41-50 years which were 18% and 15% respectively. Mean age was 38.23 years with ages ranging from 4 to 73 years. The most common presenting symptom was headache (53%), followed by vomiting (28%).The most common anatomical site was found to be cerebrum (81%), followed by ventricular and periventricular regions (6%). Supratentorial tumours (91%) were predominant over infratentorial tumours (9%). Histologically, the most common variety was found to be Glioblastoma Multiforme(30%) followed by Grade II Astrocytoma (15%) and GradeIII Astrocytoma (15%). Patients were mostly seen to be belonging to Lower Assam region (46%) . Among all the patients in the study, surgery was done for 90% of patients while 10% did not undergo surgery. 61% of the patients took radiotherapy and chemotherapy, 22% took radiotherapy alone, 7% defaulted treatment(drop outs) and 10% didn’t turn up for treatment. All patients received a radiation dose of 54-60 Gy. A total of 41 patients took adjuvant chemotherapy with Temozolomide. Conclusion: Glioblastoma Multiforme and Astrocytoma are the most common brain tumours in our study. Multimodality management including surgery, radiotherapy and chemotherapy is the cornerstone in the management of brain tumours.